Actualization of Pancasila as the Foundation of Indonesian Political Law - Nurani, Namira (Journal of Creativity Student, 2018)
Pancasila is a major cornerstone in the making of law (law and Legislation) with a new or replacement of law (political law), so that the values of the Deity, Humanity and Society (nationalistic; democratic; social justice) must be actualized into the substance of the law, the legal structure and legal culture to be built, is expected to strengthen national integration, democratization of law, achieve prosperity and social justice by putting pancasila, ranging from values, goals until the actualization of the various fields of existing law, whether criminal, civil, administrative and the other, as well as the internalization of the structures of law and legal culture of pancasila.